THE EFFECT OF THE REMAINING BUDGET CALCULATIONS AND BUDGET REFOCUSING ON EXPENDITURE FOR COVID-19 HANDLING - Nova, Indana; Andayani, Tutut Dwi; Hidayah, Rini (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This study investigates the effect of the Remaining Budget Calculation and Budget Refocusing on Expenditure for Handling Covid-19 in districts/cities governments in Central Java in 2020-2021. This study took the population of district/city governments in Central Java. This study used a purposive sampling method in order to obtain 20 districs/cities that were feasible to study. This study uses multiple linear regression analysis techniques. The results obtained show that Remaining Budget Calculations and Budget Refocusing have a simultaneous effect on Expenditure for Handling Covid-19. Partially, the Budget Refocusing variable has an effect on Expenditure for Handling Covid-19, while the Remaining Budget Calculation has no effect on Spending for Handling Covid-19 in Regency/City Governments in Central Java in 2020-2021. The coefficient of determination in this study is 46.8%, which means that the ability of all independent variables in the form of Remaining Budget Calculations and Budget Refocusing in explaining the dependent variable in the form of Covid-19 Handling Expenditures is 46.8% and the remainder is influenced by variables outside the regression model.